Estimation of Mineral Ca, Mg, Fe, Cu and Zn Content in Common Fish of Bangladesh - Mamun, Md Abdullah Al; Ghani, Ruhina Binta A; Sidiquee, Mohammad Ali; Islam, Sheikh Nazrul (Bangladesh Journal of Nutrition, 2019)
The present article reports the content of mineral content (Ca, Mg, Fe, Cu and Zn), and moistute in some indigenous fishes. Mineral contents were determined by Atomic Absorption Spectrophotometer (AA-6800) after appropriate digestion of the fish samples, and moisture was determined by AOAC method. Calcium and magnesium content were found to be highest in Mola (Amblypharyngodon mola) followed by Ketchki (Coria soborna), the iron, copper and zinc amounts were higher in Ketchki (Coria soborna) than the Mola (Amblypharyngodon mola) fish. The other fishes contained little amounts of these minerals compared to the Mola and ketchki. Moisture content was in a range of 71.90 g % in Pangas to 80.73 g % in Ketchki. The Mola and ketchki are very rich in mineral contents (Ca, Mg, Fe, Cu and Zn), regular intake of which would certainly fill up the mineral deficiency of the people. Bangladesh J. Nutr. Vol. 32, December 2019, P: 57-59